Connotations of Animal Metaphors in the Jordanian Context - Хаді Хамдан; Ханан М. Аль-Маданат; Ваель Дж. Хамдан (Психолінгвістика, 2023)
Purpose. This paper examines the connotations of the most common ten animal metaphors in the Jordanian context as perceived by Jordanian Arabic speakers.